How pollen tubes fight for food: the impact of sucrose carriers and invertases of Arabidopsis thaliana on pollen development and pollen tube growth - Seitz, Jessica; Reimann, Theresa Maria; Fritz, Carolin; Schröder, Carola; Knab, Johanna; Weber, Walter; Stadler, Ruth (Frontiers in Plant Science, 2023)
Pollen tubes of higher plants grow very rapidly until they reach the ovules to fertilize the female gametes. Here, we studied the function of sucrose transporters and invertases during pollen germination and pollen tube growth. The genome of Arabidopsis thaliana contains eight genes that encode functional sucrose/H+ symporters. Apart from AtSUC2, which is companion cell specific, all other AtSUC genes are expressed in pollen tubes. AtSUC1 is present in developing pollen and seems to be the most important sucrose transporter during the fertilization process. Pollen of an Atsuc1 knockout mutant contain less sucrose and have defects in pollen germination and in pollen tube growth. The loss of other sucrose carriers affects neither pollen germination nor pollen tube growth. A multiple knockout line Atsuc1Atsuc3Atsuc8Atsuc9 showed a mutant phenotype that is comparable to the Atsuc1 mutant line. Loss of AtSUC1 can`t be complemented by AtSUC9, suggesting a special function of AtSUC1. AtSUC4 is the only sucrose carrier localized in the tonoplast, transporting sucrose from the vacuole into the cytosol. AtSUC4 is also expressed in pollen tubes and in cells of the stigma, however, Atsuc4 knockout mutants show normal pollen tube growth. Besides sucrose carriers, pollen tubes also synthesize monosaccharide carriers of the AtSTP family as well as invertases. We could show that AtcwINV2 and AtcwINV4 are expressed in pollen, AtcwINV1 in the transmitting tissue and AtcwINV5 in the funiculi of the ovary. The vacuolar invertase AtVI2 is also expressed in pollen, and a knockout of AtVI2 leads to a severe reduction in pollen germination. Our data indicate that AtSUC1 mediates sucrose accumulation during late stages of pollen development and cleavage of vacuolar sucrose into monosaccharides is important for the process of pollen germination.